Habitat-use strategy of th European eel Anguilla anguilla in Italian waters as indicated by otolith SR/CA ratios - Li, DY; Capoccioni, F; Iizuka, Y; Tzeng, WN; CICCOTTI, ELEONORA (country:CN, 2011)
THE SR/CA RATIO IN FISH OTOLITHS CAN REFLECT THE SALINITY OF HABITATS, AND IS WIDELY USED TO RECONSTRUCT THE PAST MIGRATORY ENVIRONMENTAL HISTORY OF FISH. TO UNDERSTAND THE HABITAT USE AND MIGRATORY BEHAVIOR OF THE EUROPEAN EEL (ANGUILLA ANGUILLA) IN 3 DIFFERENT SALINITY HABITATS, TEVERE RIVER (TR, MONTHLY AVERAGE SALINITY = 0.0PSU), LESINA LAGOON (LL, 16.0±11.4 PSU), AND CAPROLACE LAGOON (CL, 38.1±4.5 PSU), SOUTHERN ITALY. THE SR/CA RATIOS IN OTOLITHS FROM PRIMORDIUM TO OTOLITH EDGE OF THE EEL WERE MEASURED BY ELECTRON PROBE MICRO-ANALYZER BASED ON THE 47 INDIVIDUALS RANDOMLY SELECTED FROM THE 180 EELS COLLECTED IN THE 3 HABITATS. THE RELATIONSHIP BETWEEN THE OTOLITH SR/CA RATIOS AND AMBIENT SALINITY WAS POSITIVELY CORRELATED (R2=0.63, P<0.01), WHICH FURTHER CONFIRMED THAT THE SR/CA RATIO IS A RELIABLE PROXY IN STUDYING THE MIGRATORY ENVIRONMENT HISTORY OF THE EEL. THE MEAN(RANGE) SR/CA RATIOS IN OTOLITH FROM ELVER STAGE UNTIL OTOLITH EDGE FOR THE EEL COLLECTED FROM TR, LL AND CL WERE 3.2±2.9 MMOL/MOL (0.3-6.1 MMOL/MOL), 7.8±4.2 MMOL/MOL (3.6-12MMOL/MOL) AND 10.1±3.9 MMOL/MOL (6.2-14MMOL/MOL), WHICH CORRESPONDED TO FRESHWATER, BRACKISH AND SEAWATER MIGRATORY CONTINGENTS, RESPECTIVELY. HOWEVER, THE PROPORTION OF INTER-HABITAT SHIFTERS WAS HIGHER IN THE POORLY PRODUCTIVE LAGOON AND LOWER IN THE RICHLY PRODUCTIVE BRACKISH LAGOON. THIS STUDY DEMONSTRATES THAT THE FACULTATIVELY CATADROMOUS MIGRATION OF EUROPEAN EEL WAS CONDITIONAL.